656. Development and Application of a Pragmatic Algorithm for the Detection of Carbapenemase-Producing Pseudomonas aeruginosa (CP-PA). (31st December 2020) - Gill, Christian M; Asempa, Tomefa E; Nicolau, David P
Abstract: Background: Historically, carbapenem-resistance in P. aeruginosa (PA) has been mediated by inducible AmpC, drug efflux, and porin loss; however, carbapenemase production is an increasingly recognized entity. Of these mechanisms, carbapenemases can drastically reduce treatment options and rapidly disseminate. Since broad applications of phenotypic (mCIM/eCIM) and PCR-based detection can be labor intensive and costly, we developed an MIC derived algorithm to streamline use of these definitive carbapenemase detection methodologies. Methods: To develop the testing criteria, a challenge set of PA (n=92), NDM, IMP, VIM, KPC, SPM, GES, cephalosporinase or efflux/porin mutation and wild-type isolates were utilized. Broth microdilution MICs were determined for: ceftazidime (CAZ), cefepime (FEP), piperacillin/tazobactam (TZP), meropenem (MEM), imipenem (IPM), ceftolozane/tazobactam (C/T), and ceftazidime/avibactam (CZA). To assess the utility of CAZ, FEP, TZP, and C/T screening criteria from the challenge set, 1, 209 clinical PA isolates from a US surveillance program were tested. Confirmatory genotypic and phenotypic testing for evidence of carbapenemases was conducted on all criteria-derived isolates using the Xpert Carba-R assay and the modified carbapenem inactivation method (mCIM)/EDTA-modified carbapenem inactivation method (eCIM), respectively. Results: Test performance and characteristics of the challenge set are displayed in Table 1. Of the 1, 209 clinical isolates, 230 (19%) were IPM and MEM resistant. 116 isolates met the defined criteria (using most common anti-pseudomonal β-lactams) of: IPM and MEM resistance; non-susceptibility to CAZ, FEP, and TZP. Carba-R identified 5 carbapenemase-producing isolates (all bla VIM -positive), while the mCIM/eCIM detected 7 carbapenemase-producing isolates (including the 5 bla VIM -positive isolates). Table 1. Characteristics of the Challenge Set of 92 P. aeruginosa isolates utilized in algorithm development. Conclusion: In the presence of carbapenem resistance, non-susceptibility to FEP, CAZ, and TZP (or C/T when available) is a useful starting point to delineate CP-PA versus non-CP-PA. This MIC criterion combined with either mCIM/eCIM or PCR-based testing is a pragmatic and streamlined approach to identify CP-PA, while providing vital information to guide therapeutic and infection control measures. Disclosures: David P. Nicolau, PharmD, Cepheid (Other Financial or Material Support, Consultant, speaker bureau member or has received research support.)Merck & Co., Inc. (Consultant, Grant/Research Support, Speaker's Bureau)Wockhardt (Grant/Research Support)